ANALYSIS OF DOMESTIC VIOLENCE PREVENTION IN ISLAMIC LAW AND LAW PERSPECTIVE - Khrisna Hadiwinata; Shohib Muslim; Hudriyah Mundzir (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2021)
Abstract Domestic violence can happen to anyone regardless of social status or economic situation. Based on Article 1 point 1 of Law Number 23 of 2004 concerning the Elimination of Domestic Violence, it is stated that Domestic Violence is any act against a person, especially a woman, which results in physical, sexual, psychological misery or suffering, and/or neglect of the household. including threats to commit acts, coercion or unlawful deprivation of liberty within the household. The protection provided by the Domestic Violence Law supports the right of citizens to feel safe and free from all forms of violence. Protection for citizens against domestic violence is in accordance with the philosophy of Pancasila and the 1945 Constitution of the Republic of Indonesia. Keywords : Socialization, mentoring, domestic violence